Extracellular Vesicles: Recent Insights Into the Interaction Between Host and Pathogenic Bacteria - Zou, Chaoyu; Zhang, Yige; Liu, Huan; Wu, Yu; Zhou, Xikun (Frontiers in Immunology, 2022)
Extracellular vesicles (EVs) are nanosized lipid particles secreted from eukaryotic cells. EVs carry bioactive molecules, shuttle from cells to cells and transduce signals, regulating cell growth and metabolism. Pathogenic bacteria can cause serious infections via a wide range of strategies, and host immune systems also develop extremely complex adaptations to counteract bacterial infections. As notable carriers, EVs take part in the interaction between the host and bacteria in several approaches. Generally, infection leads to changes in EVs, and these changes may protect the host against bacteria by expelling damaged membranes and bacteria, neutralizing toxins, releasing cytokines, presenting antigens and provoking immune responses in nearly the whole body, including the respiratory system, gastrointestinal system, circulatory system, urinary system and others. However, certain bacteria can escape immune killing through EVs. Due to their crucial function, EVs have great application potential in vaccines, diagnosis, treatments and industrial production. In the present review, we highlight the most recent advances, application potential and remaining challenges in understanding EVs in the interaction between the host and bacteria. We confirm that further studies of EV modification and translation are needed to verify their superior efficacy.